Digital Literacy Skills of Early Childhood in Using Gadgets - Tabrani, Muhamad Doni; Hayatina, Lamya; Nurrita, Teni (STAI Publisistik Thawalib Jakarta, 2024)
The rapid development of information technology has brought convenience to various aspects of life, one of which is through the use of gadgets. Gadgets have become part of everyday life and are popular among all age groups, including early childhood, due to their diverse features for accessing information and entertainment. Although gadget use is often viewed negatively, when used appropriately, gadgets also have the potential to enhance children's digital literacy skills. This study aims to explore the extent of digital literacy skills in early childhood in using gadgets functionally, by their developmental stage. A qualitative approach was employed, using primary data. Informants were selected through purposive sampling, including teachers, parents, and children aged 4–5. Data collection methods included interviews, observation, and documentation, with instruments developed based on components of children’s digital literacy, namely functional skills and beyond functional skills. Data were analyzed through reduction, display, and conclusion drawing/verification. The results indicate that early childhood learners can operate various applications and features on gadgets, including school-based TV apps such as Kahoot!, Quizizz, Wordwall, and Liveworksheet, as well as smartphone features such as calling, camera, games, WhatsApp, and YouTube. These findings suggest that young children are beginning to demonstrate foundational digital literacy skills that are developing well, although adult guidance and supervision remain essential in their use of technology.